Former Prime Minister H.E. General Prem Tinsulanonda and His Major Public Policies and Works (B.E.2523-2531) - nakata, thinapan (King Prajadhipok’s Institute Journal, 2020)
H.E. General Prem Tinsulanonda, former Prime Minister of Thailand (2523-2531) initiated national policies and fulfilled major works useful for the country. First, facing global economic problems, the Thai economy was still able to grow to the level of the top five Asian tigers. Financial discipline was high and the baht depreciated,the problem of unemployment was reduced, inflation decreased to normal level and the policy for domestic energy development was adopted. Second, Thailand faced with ideological division, internal stability, and rural poverty. These led to the announcement of the Prime Minister’s Office Order No.66/2523, which eventually ended civil war, communism, terrorism, and separatism satisfactorily. In particular, the government was able to solve the problems of rural poverty by implementing the 10 year Rural Development Plan. And third, General Prem Tinsulanonda was able to preserve Thai democracy for eight years. He suppressed two attempted of coups d’état and oversaw three general elections. Thailand was the Leader of ASEAN and got a representative on the UN Security Council for the first time. With his leadership and honesty, General Prem Tinsulanonda utilized human resources from various sectors and formed special committees to solve problems. He also gave major roles to the Finance Ministry, the Budget Bureau, the Bank of Thailand, and the National Economic and Social Development Board (NESDB) in the development of the country.